Gender Differences in the Associations Between Perceived Parenting Styles and Young Adults’ Cyber Dating Abuse - Paleari, F. Giorgia; Celsi, Laura; Galati, Desirèe; Pivetti, Monica (Frontiers in Psychology, 2022)
Existing literature indicates that parenting styles affect the development of cyber aggression in offspring differently, depending on children gender. The present study investigates whether mothers’ and fathers’ parenting styles show similar gender differences in their associations with a new form of dating violence: cyber dating abuse (CDA). The limited evidence on the issue focuses on the relation that each parenting style has with CDA perpetration, without considering CDA victimization nor the joint effects of fathers and mothers’ parenting styles. The present study contributes to the research on gender differences in parenting by examining whether young adults’ perceptions of maternal and paternal parenting styles during childhood were independently and/or jointly related to their perpetrated and suffered CDA and whether these relations differed across young adults’ gender. 351 young adults (50.7% males), aging between 18 and 35 years and having a romantic relationship, completed online self-reports of the variables of interest, including a bidimensional measure of perpetrated/suffered CDA assessing aggression and control. Results showed that maternal authoritarian parenting was uniquely and positively associated to their children’s perpetration and victimization of cyber dating control, whereas maternal permissive parenting was uniquely and positively related to their children’s perpetration of cyber dating aggression and victimization of cyber dating control. For daughters these associations were stronger when the father’s style was similar to the mother’s one or when a maternal authoritarian parenting combined with a paternal permissive style, thus indicating that the two parents’ parenting styles interact in relating to their daughters’ CDA.